Everything you always wanted to know about sex and dopamine, but were afraid to ask - Müller, Christian P. (Journal of Neurochemistry, 2019)
Behavioral neuroscience has taken a long time to finally recognize that the largely distinct behavioral repertoires of males and females may arise from differences in brain function. This may in particular apply for the neurochemistry of the dopamine systems and their roles in the organization of emotion, learning, and reinforcement in health and in pathological conditions. The current Editorial highlights a study by Egenrieder and colleagues published in the current issue of the Journal of Neurochemistry, in which the authors have analyzed extracellular dopamine neurochemistry from females and males in a meta-analysis. Largely surprising, they report that after detailed control of methodological differences between studies, no major differences in basal or drug-induced extracellular dopamine activity emerged between sexes in rodents. The locally dissociating effects of ovariectomy in females reported in the Egenrieder et al. study, may furthermore suggest that there may be different sex effects in the distinct dopaminergic projections of the mesolimbic and nigrostriatal dopamine system. However, this may only be the beginning of a system's analysis of dopaminergic sex differences that calls for further meta-analyses of the existing studies.
CRIS-Team WoS Importer:2019-12-10